Mean cover and frequencies of vascular plant species during three decades around Abisko Scientific Research Station - Henrik Hedenås; Bengt Å Carlsson; Urban Emanuelsson; Alistair D Headley; Christer Jonasson; Brita M Svensson; Terry V Callaghan (PANGAEA, 2012)
Plant species distributions are expected to shift and diversity is expected to decline as a result of global climate change, particularly in the Arctic where climate warming is amplified. We have recorded the changes in richness and abundance of vascular plants at Abisko, sub-Arctic Sweden, by re-sampling five studies consisting of seven datasets; one in the mountain birch forest and six at open sites. The oldest study was initiated in 1977-1979 and the latest in 1992. Total species number increased at all sites except for the birch forest site where richness decreased. We found no general pattern in how composition of vascular plants has changed over time. Three species, Calamagrostis lapponica, Carex vaginata and Salix reticulata, showed an overall increase in cover/frequency, while two Equisetum taxa decreased. Instead, we showed that the magnitude and direction of changes in species richness and composition differ among sites.
Supplement to: Hedenås, H et al. (2012): Changes versus homeostasis in Alpine and Sub-Alpine vegetation over three decades in the Sub-Arctic. AMBIO, 41(S3), 187-196, https://doi.org/10.1007/s13280-012-0312-3